Synthesis and characterization of new diiodocoumarin derivatives with promising antimicrobial activities - Mohamed, Hany M.; EL-Wahab, Ashraf H. F. Abd; EL-Agrody, Ahmed M.; Bedair, Ahmed H.; Eid, Fathy A.; Khafagy, Mostafa M.; Abd-EL-Rehem, Kamal A. (Beilstein Journal of Organic Chemistry, 2011)
A series of 6,8-diiodocoumarin-3-N-carboxamides (4–11) were prepared. Treatment of ethyl 6,8-diiodocoumarin-3-carboxylate (1) with ethyl cyanoacetate/NH4OAc gave ethyl 2-(3-carbamoyl-6,8-diiodocoumarin-4-yl)-2-cyanoacetate (12) and 2-amino-4-hydroxy-7,9-diiodocoumarino[3,4-c]pyridine-1-carbonitrile (13), and treatment with acetone in the presence of NH4OAc or methylamine gave the ethyl 4-oxo-2,6-methano-2-methyl-3,4,5,6-tetrahydro-8,10-diiodobenzo[2,1-g]-2H-1,3-oxazocine-5-carboxylate derivatives 14a,b. All compounds were evaluated for their antimicrobial activity and the compounds 12–14a,b exhibited a pronounced effect on all tested microorganisms.
Keywords: antimicrobial; 3,5-diiodosalicylaldehyde; diethyl malonate; ethyl cyanoacetate; coumarins; Michael reaction